Catalytic Knockdown of miR-21 by Artificial Ribonuclease: Biological Performance in Tumor Model - Patutina, Olga A.; Miroshnichenko, Svetlana K.; Mironova, Nadezhda L.; Sen’kova, Aleksandra V.; Bichenkova, Elena V.; Clarke, David J.; Vlassov, Valentin V.; Zenkova, Marina A. (Frontiers in Pharmacology, 2019)
Control of the expression of oncogenic small non-coding RNAs, notably microRNAs (miRNAs) is an attractive therapeutic approach. We report a design platform for catalytic knockdown of miRNA targets with artificial, sequence-specific ribonucleases. miRNases comprise a peptide [(LeuArg)2Gly]2 capable of RNA cleavage conjugated to the miRNA-targeted oligodeoxyribonucleotide, which becomes nuclease-resistant within the conjugate design, without resort to chemically-modified nucleotides. Our data presented here showed for the first time a truly catalytic character of our miR-21-miRNase and its ability to cleave miR-21 in a multiple catalytic turnover mode. We demonstrate that miRNase targeted to miR-21 (miR-21-miRNase) knocked down malignant behavior of tumor cells, including induction of apoptosis, inhibition of cell invasiveness and retardation of tumor growth, which persisted on transplantation into mice of tumor cells treated once with miR-21-miRNase. Crucially, we discover that the high biological activity of miR-21-miRNase can be directly related not only to its truly catalytic sequence-specific cleavage of miRNA, but also to its ability to recruit the non-sequence specific RNase H found in most cells to elevate catalytic turnover further. miR-21-miRNase worked synergistically even with low levels of RNase H. Estimated degradation in the presence of RNase H exceeded 103 miRNA target molecules per hour for each miR-21-miRNase molecule, which provides the potency to minimize delivery requirements to a few molecules per cell. In contrast to the comparatively high doses required for the simple steric block of antisense oligonucleotides, truly catalytic inactivation of miRNA offers more effective, irreversible and persistent suppression of many copy target sequences. miRNase design can be readily adapted to target other pathogenic microRNAs overexpressed in many disease states.